Money Politics VS Cost Politics: Memilih Makna Yang Terlihat Sama - Nova Nazwa Ramadhanti; Sahrul Sodikin; Siti Abelia Puteri; Noerma Kurnia Fajarwati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article explores the comparison between money politics and cost politics in the context of the political process and its influence on democratic integrity. Money politics reflects corrupt practices in which wealth is used to manipulate election outcomes or political decisions, while cost politics includes costs related to campaigns, regulations, and citizen participation in the political process. In distinguishing these two concepts, this article highlights their role in shaping the strengths and weaknesses of democracy and the challenges in strengthening political integrity. By analyzing case studies and theoretical concepts, this article aims to present a clearer understanding of the differences between money politics and cost politics, as well as promote efforts to address corruption and increase transparency in the political process.